Revision of Euliroetis Ogloblin, 1936 (Coleoptera: Chrysomelidae: Galerucinae) from China, with descriptions of two new species - Feng, Chuan; Huang, Zheng-Zhong; Yang, Xing-Ke; Ge, Si-Qin (Zootaxa, 2024)
In this study, based on the examination of type specimens, the morphology of male and female genitalia and additional body characters, the leaf-beetle genus Euliroetis is taxonomically revised. Five Chinese species of Euliroetis are redescribed, a new synonymy is proposed: E. nigrinota Gressitt et Kimoto, 1963 = E. simulonigrinota Yang, 1992, syn. nov., and two new species are described: E. testacea Feng et Yang, sp. nov. and E. tenuis Feng et Yang, sp. nov. Additionally, photographs of all male adults and genitalia, female genitalia, line drawings of all males' abdomens, and a key to species of Euliroetis is provided.